Indirect Evidences of Wildlife Activities in Shoals of Western Ghats, a Biodiversity Hotspots - Manjari Jain; Singha Roy Utpal; Mukhopadhyay, S.K. (Вестник зоологии, 2011)
The presence of wildlife fauna and its activities were ascertained with the density of the scat, dung and other markings or droppings of the wildlife abode therein. Attempt was made to find out spatial differences in the activities of the wildlife populations and to comment on the abundance of different preys and predators within shola forests of Western Ghat hill forests, a Biodiversity hotspot in India. An indirect sampling method, Transect Count Method, was employed to count dung/pellet group/scat and other markings in that area. Pachyderms were found to be mostly dominant in Varagaliar and Punnumala shola patches while scats of all the three important predators, viz., tiger (Panthera tigris tigris), Indian wild dog (Cuon alpinus) and leopard (Panthera pardus) were encountered only in Varagaliar shola. Greater abundance was recorded from Indira Gandhi Wildlife Sanctuary than Silent Valley National Park may be because of the restriction of animal movements in the former due to topographical barriers and its existence as isolated shola patches that led to a greater concentration of wild fauna in a relatively segregated forest cover Присутствие организмов в природной среде и их жизнедеятельность были установлены по плотности распределения экскрементов и других меток животных в исследованных местах. Были сделаны попытки найти отличия в жизнедеятельности популяций диких животных, и прокомментировать многообразие хищников и их жертв в лесах шола, местах наибольшего биоразнообразия в Индии. Метод косвенных образцов и метод трансектного подсчета были использованы для подсчета экскрементов/погадок и других меток в исследуемом регионе. Установлено, что на небольших участках земли в шола Варагалиар и Пуннумала доминируют толстокожие, тогда как экскременты хищников – тигра (Panthera tigris tigris), красного волка (Cuon alpinus) и леопарда (Panthera pardus) – были случайно обнаружены только в шола Варагалиар. Значительно большее количество было зарегистрировано в Заповеднике дикой природы им. Индиры Ганди по сравнению с Национальным парком «Тихая Долина», возможно, из-за ограничения миграций животных топографическими барьерами в прошлом, что привело к большей концентрации дикой фауны в относительно обособленном лесу.